A Note on Luke's Parable of the Minas and the Ancient Practice of Burying Coin Hoards - Giambrone, Anthony 1977- (2019)
The archaeology of ancient coin hoards and some basic numismatic analysis help to understand certain cultural presuppositions informing Luke's tangled discourse in his Parable of the Minas. Stories of political unrest and stories of hidden treasure naturally belong together.
Keywords: Fear; mina; Numismatics; talents; treasure